2014
DOI: 10.1371/journal.pone.0093089
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Neural Adaptation to Simultaneous Bifocal Images

Abstract: Simultaneous vision is an increasingly used solution for the correction of presbyopia (the age-related loss of ability to focus near images). Simultaneous Vision corrections, normally delivered in the form of contact or intraocular lenses, project on the patient's retina a focused image for near vision superimposed with a degraded image for far vision, or a focused image for far vision superimposed with the defocused image of the near scene. It is expected that patients with these corrections are able to adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Also, while habitually non‐corrected astigmats show strong bias towards oriented blur (coincident with the orientation of their retinal blur), the isotropic focus shifts rapidly after astigmatic correction wear, being significant only two hours after correction . In another study we also found rapid short‐term adaptation to simultaneous vision images …”
Section: Vision Applications Of Viobio Adaptive Optics Lab Technologiesmentioning
confidence: 50%
See 1 more Smart Citation
“…Also, while habitually non‐corrected astigmats show strong bias towards oriented blur (coincident with the orientation of their retinal blur), the isotropic focus shifts rapidly after astigmatic correction wear, being significant only two hours after correction . In another study we also found rapid short‐term adaptation to simultaneous vision images …”
Section: Vision Applications Of Viobio Adaptive Optics Lab Technologiesmentioning
confidence: 50%
“…[30][31][32] In another study we also found rapid short-term adaptation to simultaneous vision images. 33 The strong bias towards the native blur suggests that the eye is adapted to its own aberrations. We also used AO to investigate whether the spatial coding in the visual system is matched to the native blur specific to an individual's HOAs in terms of amplitude 34 and pattern orientation.…”
Section: Testing Spatial Adaptation With Adaptive Opticsmentioning
confidence: 99%
“…In the area of myopia management, the role of relative myopic retinal blur as a 'stop' signal for eye growth is building in the evidence base of clinical effectiveness. Radhakrishnan et al 55 examined the effect of simultaneous vision from a bifocal correction. Shifts in the perception of blur were observed with simultaneous vision bifocal designs, and the magnitude of the shifts in perception were related to the proportions of defocus.…”
Section: Blur Adaptation and Myopiamentioning
confidence: 99%
“…In addition, the ability to perform measurements with and without the natural aberrations gives insight into the needs for the correction to be selected on an individual basis or alternatively whether the same correction works similarly across a larger population (Vinas et al 2015b, Vinas et al 2016). AO systems are able to predict both visual performance and short-term adaptation to new corrections before these are implanted in the eye or even manufactured (Radhakrishnan et al 2014)…”
Section: Adaptive Optics For Visual Evaluationmentioning
confidence: 99%